Co-occurrence of kdr Mutations V1016I and F1534C and Its Association With Phenotypic Resistance to Pyrethroids in Aedes aegypti (Diptera: Culicidae) Populations From Costa Rica. Issue 3 (31st December 2019) - Zardkoohi, Aryana; Castañeda, David; Lol, Juan C; Castillo, Carmen; Lopez, Francisco; Marín Rodriguez, Rodrigo; Padilla, Norma
Abstract: Aedes aegypti (Linnaeus, 1762) is considered the most important mosquito vector species for several arboviruses (e.g., dengue, chikungunya, Zika) in Costa Rica. The primary strategy for the control and prevention of Aedes -borne diseases relies on insecticide-based vector control. However, the emergence of insecticide resistance in the mosquito populations presents a significant threat to these prevention actions. The characterization of the mechanisms driving the insecticide resistance in Ae. aegypti is vital for decision making in vector control programs. Therefore, we analyzed the voltage-gated sodium channel ( VGSC ) gene for the presence of the V1016I and F1534C kdr mutations in Ae. aegypti populations from Puntarenas and Limon provinces, Costa Rica. The CDC bottle bioassays showed that both Costa Rican Ae. aegypti populations were resistant to permethrin and deltamethrin. In the case of kdr genotyping, results revealed the co-occurrence of V1016I and F1534C mutations in permethrin and deltamethrin-resistant populations, as well as the fixation of the 1534C allele. A strong association between these mutations and permethrin and deltamethrin resistance was found in Puntarenas. Limon did not show this association; however, our results indicate that the Limon population analyzed is not under the same selective pressure as Puntarenas for the VGSC gene. Therefore, our findings make an urgent call to expand the knowledge about the insecticide resistance status and mechanisms in the Costa Rican populations of Ae. aegypti, which must be a priority to develop an effective resistance management plan.